Penggunaan LKPD Berbasis Model Discovery Learning Berbantuan Simulasi PhET untuk Meningkatkan Pengetahuan dan Keterampilan Proses Sains Siswa Kelas VIII SMPN 14 Padang - Novebrini, Sintya; Salamah, Ummi; Agustin, Silvia; Azmi, Nurul (Jurnal Penelitian Pembelajaran Fisika, 2021)
This classroom action research aims to improve students' knowledge and science process skills by using PhET simulation assisted by worksheets based on discovery learning models. The research method used is classroom action research. The subjects of this study were students of class VIII.5 SMPN 14 Padang in the 2020/2021 semester II academic year, totaling 30 people. This research was carried out in two learning cycles, with the stages in each cycle being planning, action, observation/evaluation, and reflection. This research is said to be successful if the average value of the student's scientific process ability is 80. The data that has been collected was analyzed descriptively. The results of data analysis can be stated that the use of PhET simulation assisted by LKPD based on the discovery learning model can improve student learning outcomes which include aspects of knowledge and science process skills. Data analysis 1) aspects of students' knowledge in the first cycle obtained an average value of 65.25 with a standard deviation of 8.45 while in the second cycle it was 80.45 with a standard deviation of 12.35; 2) the aspect of science process skills in the first cycle is 75.67 with a good category while in the second cycle is 90.50 with a very good category. Thus, the use of PhET simulation assisted by LKPD based on the discovery learning model has had a positive effect in increasing knowledge and skills of science processes.